Studi Pengembangan Sistem Transportasi Penyeberangan Pulau Seram-Ambon - Hanok Mandaku (ARIKA, 2012)
Transportation of connective crossing of Ceram Island and Island Ambon during the time only reliing on one line in Waipirit-Hunimua. Though, since 2003, Ceram Island as part of Central Moluccas region have been bloomed to become 3 Sub-Province, namely Central Moluccas (mains), West Ceram and East Ceram, so that mobility and accesibility at this region mount fast enough, including exploiting (supply) line of Waipirit-Hunimua. If this condition (transportation systems) remain to be defended, hence will happened demand over, which supply cannot make balance to demand. By him, require to analyse to possibility of development of crossing transportation systems by considering potency area demand of payload. This research study location alternative development of port of crossing of Ceram Island to Hunimua, analysing operational pattern and of desain conceptual of port, and also analysis competent of its development economically Result of research conclude that port of Ina-Marina in Masohi can be selected alternatively crossing transportation of Ceram Island (Masohi) to Island of Ambon (Hunimua), where proposed to operational pattern consist of (a) ship type of ro-ro; (b) speed of operational 9 knot; (c) ship frequency 2 trip / day; (d) time go through 4 hours; (e) the amount of armada 1 unit; (f) the amount of dock 1; and (g) distance of 35 mile. While conceptual desain of developed to port consist of territorial water room facility, terminal building facility for the width of 160 m2 and areal park for the width of 319 m2. For economic analysis, NPV 21.400.058.515,53.-; BCR 1,5238; and tired BEP in the year third, so that decision to develop this competent alternative economically.